Uji Kuat Tekan Beton dengan Campuran Air Asam dari Daerah Gambut - Alphario Raymond (Jurnal Serambi Engineering, 2025)
The assessment of concrete's compressive strength is of paramount importance in determining the quality of the concrete mixture and its subsequent curing process. The utilisation of water with an optimal pH level during the mixing process has been demonstrated to yield concrete of a superior quality. Despite the abundant water present in peat areas, the pH of this water is typically below ±7. Consequently, further research is necessary to ascertain the suitability of this water for use in concrete mixing. The methodology employed in this study is a quantitative descriptive study that aims to determine the impact of water with a low pH from peat areas on the concrete mixture on the resulting compressive strength. The study commenced with a review of the extant literature, followed by the testing of the concrete quality plan of 23 Mpa using water with a pH of 5.51. The curing process was conducted on days 7, 14, 28, and 90. The findings of the compressive strength examination demonstrated values of 13.1 MPa at the age of seven days, 15.3 MPa at the age of 14 days, and 15.2 MPa at the age of 28 days. Thereafter, a decline was observed at the age of 90 days, resulting in an average compressive strength of 11 MPa. The findings of this study suggest that water with a pH below 7 has a detrimental effect on the quality of concrete.